The Relationship between Learning Needs and Interest of Computer Training Participants in (LKP) Kurnia Pancung Soal, Pesir Selatan - Ramadani, Putra; Setiawati, Setiawati (Universitas Negeri Padang, 2023)
The research was motivated by the low interest of computer training participants at LKP Kurnia Computer, Pancung Soal District, Pesisisir Selatan Regency, this is thought to be related to their learning needs. The objectives of this research are 1) to describe the learning needs of computer training participants at LKP Kurnia, Pesisir Selatan Regency, 2) to describe the learning interests of computer training participants at LKP Kurnia, Pesisir Selatan Regency, and 3) to determine the relationship between learning needs and the interests of computer training participants at LKP Kurnia South Coastal Regency. This research includes quantitative research with a correlational type, the population in this study was 30 people. The sample in this research was 70% of 30 people, namely 20 people. The data collection technique is a questionnaire with a data collection tool using an instrument containing a list of statements or questions. The data analysis technique in the research is percentage using the Spearman Rho correlation formula. The results of the research can be seen: 1) Learning needs at LKP Kurnia Computer are categorized as poor, 2) interest in learning at LKP Kurnia Computer based on all sub-variables is categorized as low, and 3) there is a significant relationship between learning needs and interest in learning at LKP Kurnia Computer.Keywords: Learning needs, learning interests, course institutions